ANALISIS KREATIVITAS PESERTA DIDIK DALAM MENGGUNAKAN ALAT PERMAINAN EDUKATIF (APE) BALOK SUSUN BERWARNA DI TK - Musdalifa, Umi; Halimah, Andi; Alwi, Besse Marjani (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This study examines in depth the role of the implementation of the Ministry of Finance's Sakti Web in optimizing the productivity of making Payment Orders (SPM) at the Office of the Ministry of Religious Affairs (Kankemenag) of Hulu Sungai Utara Regency. Using a qualitative approach with a case study design, data collection was carried out through in-depth interviews with related employees, participatory observation of the work process, and analysis of SPM documents and financial reports. The results of the study significantly indicate that the Ministry of Finance's Sakti Web has succeeded in increasing the efficiency of the SPM making process. This integrated system cuts down on manual workflows, substantially reducing the time required to complete each SPM document, thus allowing for a faster response in budget realization. Furthermore, the implementation of the Ministry of Finance's Sakti Web has contributed positively to increasing transparency and accountability in financial management at the Hulu Sungai Utara Kankemenag. Each stage of the transaction is recorded digitally, facilitating tracking and auditing, and minimizing the potential for human error. However, this study also identified several challenges, mainly related to the difficulty of some employees in adapting to new technologies and complex systems. This underscores the urgent need for a more comprehensive and sustainable training program. Overall, the Ministry of Finance's Sakti Web has had a significant positive impact on employee productivity, freeing up their time to concentrate more on other strategic tasks such as program planning and improving religious services. The main recommendation of this study is the importance of institutional commitment to provide ongoing technical support and training to maximize the potential of system utilization and ensure smooth digital transformation. These findings are expected to be a valuable reference for other government agencies in their efforts to adopt information technology to improve public administration performance and service quality. ABSTRAKPenelitian kualitatif deskriptif ini menginvestigasi kreativitas anak usia dini dalam memanfaatkan Alat Permainan Edukatif (APE) berupa balok susun berwarna di TK Dunia Anak Islam Kota Kendari. Dengan sumber data berasal dari kepala sekolah dan guru, penelitian ini menggunakan metode observasi, wawancara, serta dokumentasi untuk pengumpulan data, yang kemudian dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil studi mengungkapkan bahwa penggunaan APE balok susun berwarna secara signifikan mendukung perkembangan kognitif anak, yang tercermin dalam peningkatan kemampuan berpikir, pemecahan masalah, dan elaborasi ide. Selain itu, aspek fisik-motorik juga terasah melalui peningkatan koordinasi mata-tangan, kecepatan, dan ketepatan dalam mengikuti instruksi. Dari sisi sosial-emosional, APE ini mendorong interaksi positif antar peserta didik melalui kerjasama, berbagi gagasan, dan pengelolaan emosi. Faktor-faktor yang mendukung kreativitas meliputi stimulus visual yang menarik dari balok, pendekatan pembelajaran melalui bermain, kolaborasi dalam kelompok, serta fleksibilitas balok itu sendiri. Namun, terdapat pula faktor penghambat seperti keterbatasan jumlah dan variasi balok, tingkat imajinasi anak yang beragam, aspek sosial-emosional individu, dan kompleksitas tugas yang diberikan. Upaya guru dalam mengatasi kendala ini mencakup penyediaan variasi bahan yang lebih banyak, pemberian waktu eksplorasi yang cukup, penciptaan lingkungan yang kondusif untuk eksperimen, fasilitasi interaksi positif, serta dorongan untuk berbagi dan belajar bersama.